Study the fire resistance of desert sand concrete (DSC) with interface phase through uniaxial compression tests and analyses - Zhang, Qian; Liu, Haifeng; Liu, Qiang; Che, Jialing; Yang, Weiwu; Ma, Jurong; Doh, Shu Ing; Lim, Kar Sing (Hindawi, 2021)
The shortage of sand resources and high-rise building fires are becoming increasingly prominent. Desert sand (DS) with smaller particles can effectively fill the concrete voids and further improve its working performance; it is used as a fine aggregate to produce concrete. This article studied the performance of desert sand concrete (DSC) against fire resistance by using mathematical modeling for simulation. The stress-strain curves of desert sand mortar (DSM) after elevated temperatures were tested, and the constitutive model was established. By comparing the experiment and simulation results, it was verified that the model is suitable to be adopted in this study. Data from experiment and past literature can serve as parameters for the subsequent simulation. The destruction process of DSC under uniaxial compression after elevated temperature was simulated by using ANSYS. The simulation results indicated that, after elevated temperature, compressive strength reduced with increase of interface thickness. The compressive strength of DSC had a substantially linear increase as the interface compressive strength increased. For two-grade coarse aggregate, the optimum volume content was 45%, and particle size of it showed a significant effect on the compressive strength of DSC. The DSM constitutive model and simulation results can provide a sound theoretical basis and technical support for DSC engineering applications.